Optimalisasi Head Truck Maintenance untuk Meningkatkan Availability dan Reliability di PT. TPS - Kawasugi, Regiyan Drinin; Sari, Devina Puspita; Praharsi, Yugowati (Metris: Jurnal Sains dan Teknologi, 2019)
PT TPS Surabaya is a company engaged in terminal handling, especially containers. In carrying out operational activities to transport containers from the dock to the company's container yard, it uses eighty head truck fleets. Operational activities for transporting containers are carried out 24 hours a day so that maintenance is needed. Therefore, the operational head trucks do not experience sudden damage and disrupt operations. The malfunction of the device can occur due to damage to the components in the device. The design of the component replacement and the inspection intervals on the components is needed to avoid sudden component damage. Calculation of interval replacement and component checking is done by calculating the damage distribution followed by searching for index of fit and goodness of fit using Minitab software. The result showed that the inspection time interval of 1091 hours for the air system and 398.45 hours for the transmission system components. Besides, the replacement time interval for the component of the air system is 62 hours and the transmission system is 124 hours after inspection.